Review and Assessment of Poliovirus Immunity and Transmission: Synthesis of Knowledge Gaps and Identification of Research Needs. Issue 4 (28th March 2013) - Duintjer Tebbens, Radboud J.; Pallansch, Mark A.; Chumakov, Konstantin M.; Halsey, Neal A.; Hovi, Tapani; Minor, Philip D.; Modlin, John F.; Patriarca, Peter A.; Sutter, Roland W.; Wright, Peter F.; Wassilak, Steven G.F.; Cochi, Stephen L.; et al.
Abstract : With the intensifying global efforts to eradicate wild polioviruses, policymakers face complex decisions related to achieving eradication and managing posteradication risks. These decisions and the expanding use of inactivated poliovirus vaccine (IPV) trigger renewed interest in poliovirus immunity, particularly the role of mucosal immunity in the transmission of polioviruses. Sustained high population immunity to poliovirus transmission represents a key prerequisite to eradication, but poliovirus immunity and transmission remain poorly understood despite decades of studies. In April 2010, the U.S. Centers for Disease Control and Prevention convened an international group of experts on poliovirus immunology and virology to review the literature relevant for modeling poliovirus transmission, develop a consensus about related uncertainties, and identify research needs. This article synthesizes the quantitative assessments and research needs identified during the process. Limitations in the evidence from oral poliovirus vaccine (OPV) challenge studies and other relevant data led to differences in expert assessments, indicating the need for additional data, particularly in several priority areas for research: (1) the ability of IPV‐induced immunity to prevent or reduce excretion and affect transmission, (2) the impact of waning immunity on the probability and extent of poliovirus excretion, (3) the relationship between the concentration of poliovirus excreted and infectiousness to others in different settings, and (4) the relative role of fecal‐oral versus oropharyngeal transmission. This assessment of current knowledge supports the immediate conduct of additional studies to address the gaps.